The Isolation and Identification of Flavonoid Compounds Ethanol Extract from Purple Passion Fruit Peel (Passiflora edulis Sims) - Fitrah Azzahrah (PHARMACY UMI JOURNAL SYSTEM, 2023)
The isolation and identification of flavonoid compounds from the ethanol extract of purple passion fruit peel (Passiflora edulis Sims) has been carried out. The aims of this research was to determine the class of flavonoid compounds from the ethanol extract of purple passion fruit peel (Passiflora edulis Sims). About 300 grams was extracted using maceration method with 96% ethanol produces dry 33.127 grams. Preliminary identification was performed using thin layer chromatography method with eluent n-hexane: acetone (8:2), then sprayed with AlCl3 specific reagent. Isolation was done using vacum liquid chromatography method with eluent n-hexane : acetone (100:0, 90:10, 80:20, 70:30, 60:40,50:50, 40:60, 30:70, 20: 80, 10:90, 0:100). The purity was tested using two-dimensional TLC and multi-eluent TLC methods. This research obtained a pure isolate namely isolate 4. The isolate were then identified using UV-Vis spectroscopy showed absorption at a wavelength of 230 nm and 270 nm. Infrared spectroscopy showed absorbance at wave number 3483.44 cm-1 showed possibility of O-H group, reinforced the wave number 1653.00 cm-1 which indicates the possibility of a C=C group, the wave number 1238.30 cm-1 showed possibility the C-O, the wave number 808.17 cm-1 which indicates the possibility of a C-H group, as well as identification using specific reagents. The above observations showed that the isolate is a compound of the flavonoid group.